Effect of Titanium dioxide nanoparticle as an additive on the working characteristics of biodiesel-water emulsion fuel blends. Issue 9 (3rd May 2021) - Vellaiyan, Suresh; Subbiah, Arunkumar; Chockalingam, Prabha
ABSTRACT: The present article details the working characteristics of a CI engine fueled with water-emulsified SBs and TiO2 nanoadditive-incorporated emulsified SBs, and the results are compared with those of neat SB. SB with different concentrations of water (5% and 10%) and TiO2 nanoparticle (50ppm and 100ppm) were prepared using mechanical agitation and followed by an ultra-sonication process. The physiochemical properties of test fuel were measured based on EN14214 standards, and the results show a good agreement with standard limits. The experiments were carried out in a single-cylinder, four stroke, and natural aspirated diesel engine under different BMEP conditions. The emission characteristics of test fuels show that the water-emulsified SBs reduce the NOx and smoke emissions, and 10% water in SB reduces these emissions by 21.3% and 8.1% compared to pure SB at peak BMEP condition, respectively. The HC and CO emissions of water-emulsified SB seem to be higher at low-engine loads compared to SB, and this trend is reversed at high-engine loads. At peak BMEP condition, the HC and CO emissions of 10% water in SB are 16.8% and 16.7% lower than SB, respectively. As far as the performance characteristics are concerned, 10% water in SB reduces the BSFC, BSEC, and EGT by 5.4%, 13.6%, and 8.8% compared to SB at peak BMEP condition, respectively, and improves the BTE by 13.5%. An inclusion of TiO2 nanoparticle significantly improves the emissions and performance of the CI engine and an increase in the mass fraction of nanoparticle further improves the engine working characteristics.